Cell-Associated HIV-1 Unspliced-to-Multiply-Spliced RNA Ratio at 12 Weeks of ART Predicts Immune Reconstitution on Therapy - Scherpenisse, Mirte (mBio, 2021)
Incomplete restoration of CD4(+) T-cell counts on antiretroviral therapy (ART) is a major predictor of HIV-related morbidity and mortality. To understand the possible mechanisms behind this poor immunological response despite viral suppression, we longitudinally measured more than 50 virological and immunological biomarkers in a cohort of HIV-infected individuals at several time points during the first 96 weeks of virologically suppressive ART. No baseline virological or immunological marker was predictive of the degree of immune reconstitution. However, the cell-associated HIV-1 unspliced-to-multiply-spliced (US/MS) RNA ratio at 12 weeks of ART positively correlated with markers of CD4(+) T-cell activation and apoptosis and negatively predicted both the absolute and relative CD4(+) T-cell counts at 48 and 96 weeks. A higher US/MS RNA ratio may reflect the higher frequency of productively infected cells that could exert pressure on the immune system, contributing to persistent immune activation and apoptosis and subsequently to a poor immunological response to ART.